Geotechnical behavior of a compacted waste foundry sand. (29th March 2021) - Heidemann, Marcelo; Nierwinski, Helena Paula; Hastenpflug, Daniel; Barra, Breno Salgado; Perez, Yader Guerrero
Highlights: The role of the compaction effort on geotechnical behavior of waste foundry sands was investigated. Increasing of compaction effort causes remarkable changes in terms of bearing capacity and shear strength. Suction plays a remarkable role in the behavior of waste foundry sand after being air-dried. Waste foundry sand requires a rigorous compaction control. Abstract: Brazil produces more than 3 million tons of waste foundry sands (WFS) each year. Although this material presents characteristics that fulfill the environmental requirements to be recycled and used as a building material, the lack of information regarding its geotechnical behavior inhibits its use, mainly in applications that require good performance. Therefore, this study investigates the role of the compaction effort on the behavior of compacted WFS considering its application as a building material in geotechnical work. The experimental procedures include X-ray fluorescence analysis, scanning electron microscopy, determination of compaction curves, California bearing ratio (CBR), the execution of unconfined compression, direct shear, and oedometric tests. Geomechanical tests were conducted on specimens compacted with three distinct compaction efforts: 600 kJ/m 3, 1260 kJ/m 3 and 2700 kJ/m 3 . The WFS is composed mainly of quartz particles with subangular to subrounded shape. Fines are 12% of its composition, and WFS is classified as a well-graded material. Optimum moisture content ranges between 9.0 and 11.5%. The higher the compaction effort, the lower is the void ratio. Despite the differences in the void ratios are small, they affect the CBR values dramatically. Compaction effort increases friction angle and unconfined compressive strength and reduces compressibility. Suction plays a remarkable role in the behavior of such material after being air-dried. This study can contribute to a better understanding of potentialities and limitations for the use of WFS in compacted conditions.